Poplar for biodiversity? : comparison of lichen communities in stands of Balsam poplar, Hybrid larch, Silver birch and Norway spruce - Jastrzebska, Ewa Zuzanna (SLU/Southern Swedish Forest Research Centre, 2020)
Due to increasing interest in the use of non-native tree species, more knowledge is needed concerning their effects on biodiversity. In this context, epiphytic lichens were investigated in two stands of non-native tree species (Larix×eurolepis and Populus trichocarpa) and two stands of native tree species (Picea abies and Betula pendula) in a field experiment in southern Sweden. The trunks in the stands were examined separately for northern and southern side of the tree trunk. The presence of all types of lichen (crustose, foliose and fruticose) species were registered. Twenty-two lichen species in total were found in the experimental sites; six in P. abies stand, seven in B. pendula stand, nine in L.×eurolepis stand and eighteen in P. trichocarpa stand. Most of the lichen species are common in Sweden. Although one red-listed lichen species, Alyxoria ochrocheila was found. The status of this lichen is near threatened (NT). The non-metric multidimensional scaling (NMDS) had been used for displaying the diversity of lichen communities. The study showed the highest lichen community diversity and species richness in the P. trichocarpa stand. The only one red-listed lichen species, A. ochrocheila was also found in this stand. The other non-native tree species stand (L.×eurolepis) showed higher diversity and species richness than both stands of native tree species. The less lichen diverse and the poorest in lichens species was the P. abies stand. The diameter breast height was not significant for lichen richness in this study. Neither was the side of the tree on which the lichens were found. Investigated non-native tree species seem to have potential to increase biodiversity in production stands. Considering the bark complexity, fast growth and stand architecture, species like poplar may support ecological functions similar to those provided by great-dimension, old trees like oaks. It is recommended to continue the study in other parts of Sweden.